NON CONTRAST HEAD CT SCAN FINDINGS IN STROKE PATIENTS AT THE RADIOLOGY DEPARTMENT OF TIARASELLA HOSPITAL BENGKULU 2024 - Susanto, Ari; Sari, Ade Zayu Cempaka (Journal of Applied Health Management and Technology, 2025)
Stroke is the third leading cause of death in the world. Stroke is a condition with rapidly developing clinical signs in the form of focal and global neurological deficits, which can occur and last for 24 hours or more. The purpose of this study was to determine the results of head CT scans in patients with clinical stroke, both ischemic and non-hemorrhagic, in the Radiology Department of Tiarasella Hospital, Bengkulu, January-December 2024. Methods: This study is a retrospective descriptive study utilizing secondary data in the form of head CT scan request & answer sheets. Results of the study: Based on 50 patient data obtained, 74 patients were diagnosed with ischemic stroke (92%) and hemorrhagic stroke (8%). Male patients were more numerous (54%) than female patients (46%). The 56-65 year age group was the largest age group, namely 19 patients (38%) followed by those aged more than or equal to 66 years as many as 18 patients (36%); Conclusion: In patients with a radiological diagnosis of ischemic stroke, the most patients were.